2009
DOI: 10.3310/hta13170
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation for chronic pain of neuropathic or ischaemic origin: systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
3
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(190 citation statements)
references
References 66 publications
2
175
3
10
Order By: Relevance
“…It is simply composed of implanted leads in the epidural space, a generator and controller implanted under the skin of the abdomen, and an extension cable that connects them. [13] To date, SCS has been used in clinical practice for more than four decades. It has been reported that for the treatment of neuropathic conditions such as failed back surgery syndrome and complex regional pain syndrome type I, SCS is better than conventional medical treatment or reoperation in reducing pain.…”
Section: History Of Scsmentioning
confidence: 99%
“…It is simply composed of implanted leads in the epidural space, a generator and controller implanted under the skin of the abdomen, and an extension cable that connects them. [13] To date, SCS has been used in clinical practice for more than four decades. It has been reported that for the treatment of neuropathic conditions such as failed back surgery syndrome and complex regional pain syndrome type I, SCS is better than conventional medical treatment or reoperation in reducing pain.…”
Section: History Of Scsmentioning
confidence: 99%
“…In terms of the neuropathic pain etiology, SCS has been applied in the treatment of deafferentation pain, central pain, phantom limb pain (PLP), causalgia, myelopathy, oncologic pain, lumbosacral fibrosis, postherpetic neuralgia (PHN), FBSS, CRPS, reflex sympathetic dystrophy (RSD), spinal cord, brainstem or brain injury, and others (3,(13)(14)(15)22,32,33,38,42,43,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57).…”
Section: Results In Pain Managementmentioning
confidence: 99%
“…[55,56] Spinal cord stimulation, which is applied more often to treat CRPS I, may also be beneficial. [57] …”
Section: Pain Neuromodulationmentioning
confidence: 99%